Nail the diagnosis: Lamivudine-induced periungual pyogenic granulomas in PLHIV - Karthick Kumar Vaitheeswaran; Neeraj Nischal; Neetu Bhari; Sudheer Kumar Arava; Naveet Wig (IDCases)
Background: Pyogenic granuloma (PG), also known as lobular capillary haemangioma, is a benign vascular proliferation that typically presents as friable, red, pedunculated papules on the skin or mucous membranes. Multiple periungual pyogenic granulomas, a unique entity within cutaneous pyogenic granulomas, most frequently occur in association with medications, including antiretroviral drugs. Clinical case: A 30-year-old male living with HIV presented with painful, progressively enlarging ulcero-proliferative lesions on the fingertips and toes, occurring 12 months after initiating highly active antiretroviral therapy (HAART) comprising Tenofovir disoproxil (300 mg), Lamivudine (300 mg), and Dolutegravir (50 mg). Examination revealed haemorrhagic, friable granulation tissue over the nail folds and paronychial areas of multiple digits. Systemic examination was unremarkable. Differential diagnoses included drug-induced PG, bacillary angiomatosis, Kaposi sarcoma, and cutaneous angiosarcoma. A biopsy confirmed the diagnosis of PG. Bartonella serology and tissue polymerase chain reaction (PCR) were negative, ruling out bacillary angiomatosis. Histopathology showed no features suggestive of Kaposi sarcoma or angiosarcoma. Among ART agents, lamivudine and indinavir have been most frequently associated with periungual PGs. The patient showed minimal improvement with topical corticosteroids, antibiotics, and debridement. Lamivudine was subsequently discontinued and ART was modified, leading to near-complete resolution of lesions over six months—supporting a diagnosis of lamivudine-induced periungual PG. Conclusion: Periungual pyogenic granulomas can lead to significant discomfort and functional impairment. This case highlights the potential role of lamivudine as a causative agent and underscores the importance of ART modification in the effective management of drug-induced PG.